Correction: Physiological and behavioural responses of wandering albatross chicks (Diomedea exulans) to novel and non-novel predators - Anais Cotton; Christophe Barbraud; Sarah Leclaire; Karine Delord; Aymeric Bodin; Antoine Stier; Cécile Ribout; Charline Parenteau; Jean-Baptiste Ferdy; Charlotte Bourgoin; Joël White; Frédéric Angelier; et al. (Journal of Comparative Physiology A, 2026)

Physiological and behavioural responses of wandering albatross chicks (Diomedea exulans) to novel and non-novel predators - Anais Cotton; Christophe Barbraud; Sarah Leclaire; Karine Delord; Aymeric Bodin; Antoine Stier; Cécile Ribout; Charline Parenteau; Jean-Baptiste Ferdy; Charlotte Bourgoin; Joël White; Frédéric Angelier; et al. (Journal of Comparative Physiology A, 2026)
In long-standing predator-prey systems, prey typically evolve costly responses to predation risk. How prey respond to novel predators is less investigated. We explored physiological (corticosterone, triglyceride), morphological (body condition) and behavioural (defensive posture) responses of wandering albatross ( Diomedea exulans ) chicks to a novel predator, the feral cat ( Felis catus ) in Kerguelen archipelago. We implemented a semi-experimental design to increase the variance in cat abundance by regulating cat populations in certain zones of the study colony. The aforementioned chick traits were then monitored and analysed at the zone scale, by comparing nests located within regulated and non-regulated zones, and at the nest scale, by recording cat abundance through intensive camera traps monitoring. This fine-scale approach further enabled us to investigate how chicks responded to southern giant petrels ( Macronectes giganteus ), an opportunistic predator-scavenger that has co-evolved with albatrosses. Cat abundances had no effect on chick traits. In contrast, higher abundances of giant petrel were associated with an elevated rate of corticosterone increase and lower triglyceride levels. In accordance with these results suggesting a more accurate perception of predation risk mediated by giant petrels than by cats, chicks were more prone to display a defensive posture when facing a giant petrel than a cat. We discuss these results in the light of contrasting evolutionary histories and predation patterns between albatrosses and their predators, and we emphasise that studies of predator impacts on prey populations must consider both the direct and indirect effects of all predators, as well as their interactions.

Environmental Variability Shapes Life‐History Trade‐Offs Within and Between Populations of a Long‐Lived Seabird - Bertille Mohring; Jonathan R. Potts; Alastair J. Wilson; Denis Réale; Richard A. Phillips; Henri Weimerskirch; Christophe Barbraud; Ashley Bennison; Karine Delord; Andrew G. Wood; Samuel Peroteau; Etienne Rouby; et al. (Ecology Letters, 2026)
Individuals face a trade‐off between allocating resources to reproduction or self‐maintenance, yet the drivers of the existence and strength of such trade‐off have been hard to determine. Environmental conditions are thought to play a crucial role, as long‐lived species are predicted to favour more precautionary life‐history strategies in variable environments. However, empirical evidence remains limited. Using long‐term monitoring of two black‐browed albatross Thalassarche melanophris populations, we investigated variation in life‐history strategies under contrasting environmental conditions, through reproductive senescence. In more variable environments, individuals displayed generally slower life histories (i.e., slow, late‐onset senescence) and greater among‐individual variation in life‐history strategies. Interestingly, earlier and faster reproductive senescence correlated with higher lifetime reproductive success regardless of environmental variability, suggesting that either faster life histories incur higher fitness or successful reproduction accelerates reproductive senescence. These findings reveal how environmental variability shapes life‐history strategies, highlighting potential responses to increasing environmental variability in a changing world.

Post-breeding season behaviour of a threatened population of subtropical brown skuas - Anne-Sophie Bonnet-Lebrun; Karine Delord; Yves Cherel; Cécile Ribout; Gaël Guillou; Paco Bustamante; Christophe Barbraud (Marine Biology, 2026)

Ecological forecasts highlight opposing effects of long‐term climate change on population demography - Francesco Ventura; Bilgecan Sen; Christian Che‐Castaldo; Christophe Barbraud; Karine Delord; Kristen Krumhardt; Marika Holland; Laura Landrum; Zephyr Sylvester; Paul Lukacs; Stéphanie Jenouvrier (Ecology, 2026)
The multifaceted impacts of global climate change on biota challenge our understanding and capability of anticipating the long‐term viability of wild populations, which is an emergent property of ecological systems. Using Bayesian integrated population modeling, sensitivity analyses, and ecological forecasting, we investigate how climate variability shapes the long‐term population dynamics of a species highly sensitive to climate change: the emperor penguin ( Aptenodytes forsteri ). Leveraging a multi‐decadal database from Pointe Géologie, East Antarctica, we assess penguin sensitivity to multiple environmental drivers and produce anticipatory projections of the emerging population trajectories under the noise of forecasted climatic changes. We found that receding fast ice during chick‐rearing, leading to reduced commuting distances to open water, improves breeding success. Conversely, ocean warming and stronger winds negatively impact adult survival, possibly due to changes in Antarctic marine productivity. These contrasting effects of ocean warming and sea ice contractions on adult survival and breeding success, the most important contributors to the realized population growth rate, indicate opposing effects of climate change on penguins. Using forecasts, we explored how these opposing forces will jointly determine long‐term emperor penguin population dynamics. We found that the increased breeding success linked to reductions in fast ice may buffer and delay population declines by over a decade. However, ocean warming and its likely repercussions to the food web and adult survival will ultimately drive population declines. While forecasting is well established in climate science, ecological forecasting faces distinct challenges, including shorter and less defined predictability horizons, greater stochasticity, and limited long‐term data. Yet, forecasts can be used to understand and anticipate population responses, which is particularly valuable, given the urgent need to define proactive conservation plans. Here, forecasts reveal contrasting demographic impacts of sea ice loss and ocean warming on emperor penguins. Our approach, adaptable to other species and systems, highlights the value of anticipatory projections for disentangling and quantifying drivers of long‐term population change.

Prioritisation of conservation areas for tropical breeding Laridae under current and future development plans - Antonio Garcia-Quintas; Adrien Brunel; Christophe Barbraud; Dennis Denis; Jérémy Omer; Sophie Lanco (Biological Conservation, 2025)

Intrinsic and extrinsic drivers of juvenile survival in emperor penguins - Ewen Le Scornec; Jimmy Allain; Gaël Bardon; Téo Barracho; Nicolas Chatelain; Karine Delord; Dominique Filippi; Cécile Ribout; Céline Le Bohec; Christophe Barbraud (Polar Biology, 2025)

Flexible foraging strategies of a tropical seabird in the western Atlantic Ocean - Júlia Jacoby; Amédée Roy; Sophie Lanco; Christophe Barbraud; Karine Delord; Leandro Bugoni; Guilherme T. Nunes (Journal of Experimental Marine Biology and Ecology, 2025)

Living with uncertainty: Using multi-model large ensembles to assess emperor penguin extinction risk for the IUCN Red List - Stéphanie Jenouvrier; Alice Eparvier; Bilgecan Şen; Francesco Ventura; Christian Che-Castaldo; Marika Holland; Laura Landrum; Kristen Krumhardt; Jimmy Garnier; Karine Delord; Christophe Barbraud; Philip Trathan (Biological Conservation, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Cannibalism in northern giant petrels ( Macronectes halli ) at Possession Island, Southern Indian Ocean - Alexandre Vong; Karine Delord; Nicolas Croizé; Célia Lesage; Lucía Llorente Zubiri; Florent Sabatier; Christophe Barbraud (Ecology, 2025)

Climate Change Impacts Pair‐Bond Dynamics in a Long‐Lived Monogamous Species - Ruijiao Sun; Rémi Fay; Francesco Ventura; Bilgecan Şen; Christophe Barbraud; Karine Delord; Kristen Krumhardt; Stéphanie Jenouvrier (Ecology Letters, 2024)
Climate change can influence populations of monogamous species by affecting pair‐bond dynamics. This study examined the impact of climate on widowhood and divorce, and the subsequent effects on individual vital rates and life‐history outcomes over 54 years in a snow petrel ( Pagodroma nivea ) population. We found that environmental conditions can affect pair‐bond dynamics both directly and indirectly. Divorce was adaptive, occurring more frequently after breeding failure and leading to improved breeding success. Divorce probabilities also increased under severe climatic conditions, regardless of prior breeding success, supporting the ‘Habitat‐mediated’ mechanisms. Overall, pair‐bond disruptions reduced subsequent vital rates and lifetime outcomes. Climate forecasts from an Atmosphere–Ocean General Circulation Model projected increased male widowhood rates due to decreased sea ice negatively affecting female survival, despite considerable uncertainty. These findings highlight the importance of environmentally induced changes in demographic and pair‐bond disruption rates as crucial factors shaping demographic responses to climate change.

A modeling approach to forecast local demographic trends in metapopulations - Thierry Chambert; Christophe Barbraud; Emmanuelle Cam; Antoine Chabrolle; Nicolas Sadoul; Aurélien Besnard (Ecology, 2024)
Predicting animal population trajectories into the future has become a central exercise in both applied and fundamental ecology. Because demographic models classically assume population closure, they tend to provide inaccurate predictions when applied locally to interconnected subpopulations that are part of a larger metapopulation. Ideally, one should explicitly model dispersal among subpopulations, but in practice this is prevented by the difficulty of estimating dispersal rates in the wild. To forecast the local demography of connected subpopulations, we developed a new demographic model (hereafter, the two‐scale model) that disentangles two processes occurring at different spatial scales. First, at the larger scale, a closed population model describes changes in metapopulation size over time. Second, total metapopulation size is redistributed among subpopulations, using time‐varying proportionality parameters. This two‐step approach ensures that the long‐term growth of every subpopulation is constrained by the overall metapopulation growth rate. It implicitly accounts for the interconnectedness among subpopulations and avoids unrealistic trajectories. Using realistic simulations, we compared the performance of this new model with that of a classical closed population model at predicting subpopulations' trajectories over 30 years. While the classical model predicted future subpopulation sizes with an average bias of 30% and produced predictive errors sometimes >500%, the two‐scale model showed very little bias ( 20%. We also applied both models to a real dataset on European shags ( Gulosus aristotelis ) breeding along the Atlantic coast of France. Again, the classical model predicted highly unrealistic growths, as large as a 200‐fold increase over 30 years for some subpopulations. The two‐scale model predicted very sensible growths, never larger than a threefold increase over the 30‐year time horizon, which is more in accordance with this species' life history. This two‐scale model provides an effective solution to forecast the local demography of connected subpopulations in the absence of data on dispersal rates. In this context, it is a better alternative than closed population models and a more parsimonious option than full‐dispersal models. Because the only data required are simple counts, this model could be useful to many large‐scale wildlife monitoring programs.

Pre-eradication updated seabird survey including new records on Amsterdam Island, southern Indian Ocean - Célia Lesage; Yves Cherel; Karine Delord; Quentin d’Orchymont; Marie Fretin; Max Levy; Andreanna Welch; Christophe Barbraud (Polar Biology, 2024)

Does strict protection status harm snake populations in a temperate forest? - Gopal Billy; Christophe Barbraud; Magali Dahirel; Xavier Bonnet (Journal for Nature Conservation, 2024)

Bottom‐up effects drive the dynamic of an A ntarctic seabird predator–prey system - Lise Viollat; Maud Quéroué; Karine Delord; Olivier Gimenez; Christophe Barbraud (Ecology, 2024)
Understanding how populations respond to variability in environmental conditions and interspecific interactions is one of the biggest challenges of population ecology, particularly in the context of global change. Although many studies have investigated population responses to climate change, very few have explicitly integrated interspecific relationships when studying these responses. In this study, we aimed to understand the combined effects of interspecific interactions and environmental conditions on the demographic parameters of a prey–predator system of three sympatric seabird populations breeding in Antarctica: the south polar skua ( Catharacta maccormicki ) and its two main preys during the breeding season, the Adélie penguin ( Pygoscelis adeliae ) and the emperor penguin ( Aptenodytes forsteri ). We built a two‐species integrated population model (IPM) with 31 years of capture–recapture and count data and provided a framework that made it possible to estimate the demographic parameters and abundance of a predator–prey system in a context where capture–recapture data were not available for one species. Our results showed that predator–prey interactions and local environmental conditions differentially affected south polar skuas depending on their breeding state of the previous year. Concerning prey–predator relationships, the number of Adélie penguin breeding pairs showed a positive effect on south polar skua survival and breeding probability, and the number of emperor penguin dead chicks showed a positive effect on the breeding success of south polar skuas. In contrast, there was no evidence for an effect of the number of south polar skuas on the demography of Adélie penguins. We also found an important impact of sea ice conditions on both the dynamics of south polar skuas and Adélie penguins. Our results suggest that this prey–predator system is mostly driven by bottom‐up processes and local environmental conditions.

Human infrastructures correspond to higher Adélie penguin breeding success and growth rate - Yann Méheust; Karine Delord; Anne-Sophie Bonnet-Lebrun; Thierry Raclot; Julien Vasseur; Jimmy Allain; Virgil Decourteillle; Charles-André Bost; Christophe Barbraud (Oecologia, 2024)

How does maternal age influence reproductive performance and offspring phenotype in the snow petrel (Pagodroma nivea)? - Sophie M. Dupont; Christophe Barbraud; Olivier Chastel; Karine Delord; Marie Pallud; Charline Parenteau; Henri Weimerskirch; Frédéric Angelier (Oecologia, 2023)

The demography of the White-headed Petrel at Mayes Island, Kerguelen - Christophe Barbraud; Dominique Joubert; Karine Delord (Journal of Ornithology, 2023)

Plant consumer innovation in skuas - Samara Danel; Gaël Bardon; Christophe de Franceschi; Léna Bureau; Christophe Barbraud; Karine Delord; Dora Biro; Francesco Bonadonna (Journal of Ornithology, 2023)

Diet, isotopic niche, and spatial distribution of the white-headed petrel (Pterodroma lessonii) at Kerguelen Islands - Yves Cherel; Karine Delord; Christophe Barbraud; Henri Weimerskirch (Polar Biology, 2022)

When the going gets tough, the tough get going: Effect of extreme climate on an Antarctic seabird's life history - Stéphanie Jenouvrier; Lise Aubry; Silke van Daalen; Christophe Barbraud; Henri Weimerskirch; Hal Caswell (Ecology Letters, 2022)
Individuals differ in many ways. Most produce few offspring; a handful produce many. Some die early; others live to old age. It is tempting to attribute these differences in outcomes to differences in individual traits, and thus in the demographic rates experienced. However, there is more to individual variation than meets the eye of the biologist. Even among individuals sharing identical traits, life history outcomes (life expectancy and lifetime reproduction) will vary due to individual stochasticity, that is to chance. Quantifying the contributions of heterogeneity and chance is essential to understand natural variability. Interindividual differences vary across environmental conditions, hence heterogeneity and stochasticity depend on environmental conditions. We show that favourable conditions increase the contributions of individual stochasticity, and reduce the contributions of heterogeneity, to variance in demographic outcomes in a seabird population. The opposite is true under poor conditions. This result has important consequence for understanding the ecology and evolution of life history strategies.

Temporal correlations among demographic parameters are ubiquitous but highly variable across species - Rémi Fay; Sandra Hamel; Martijn van de Pol; Jean‐Michel Gaillard; Nigel G. Yoccoz; Paul Acker; Matthieu Authier; Benjamin Larue; Christie Le Coeur; Kaitlin R. Macdonald; Alex Nicol‐Harper; Christophe Barbraud; et al. (Ecology Letters, 2022)
Temporal correlations among demographic parameters can strongly influence population dynamics. Our empirical knowledge, however, is very limited regarding the direction and the magnitude of these correlations and how they vary among demographic parameters and species’ life histories. Here, we use long‐term demographic data from 15 bird and mammal species with contrasting pace of life to quantify correlation patterns among five key demographic parameters: juvenile and adult survival, reproductive probability, reproductive success and productivity. Correlations among demographic parameters were ubiquitous, more frequently positive than negative, but strongly differed across species. Correlations did not markedly change along the slow‐fast continuum of life histories, suggesting that they were more strongly driven by ecological than evolutionary factors. As positive temporal demographic correlations decrease the mean of the long‐run population growth rate, the common practice of ignoring temporal correlations in population models could lead to the underestimation of extinction risks in most species.

Nest characteristics and food supply affect reproductive output of white storks Ciconia ciconia in semi-arid areas - Naouel Benharzallah; Abdelkrim Si Bachir; Christophe Barbraud (Biologia, 2022)

Variation among species and populations in bill shape and size in three planktivorous petrels - Maria I. Laranjeiro; Marc Farré; Richard A. Phillips; Petra Quillfeldt; Francesco Bonadonna; Charlene Gémard; Maximiliano Daigre; Cristián G. Suazo; Christophe Barbraud; Joan Navarro (Marine Biology, 2022)

Population dynamics of sperm whales ( Physeter macrocephalus ) in Guadeloupe, French Caribbean: A mark‐recapture study from 2001 to 2013 - Caroline Rinaldi; Renato Rinaldi; Juliette Laine; Christophe Barbraud (Marine Mammal Science, 2021)
Sperm whales are present along the Caribbean islands in family groups of mature females, juveniles, and newborns. Their abundance and demographic rates remain poorly known. Using photo‐identification data, we estimated the abundance and annual survival of sperm whales in Guadeloupe from January to April 2001–2013. A total of 1,492 photographs of tail flukes were scored (ranging from 1 to 5) in terms of quality ( Q ) and marking ( M ) level. A total of 789 photographs were selected with Q ≥ 3 and M ≥ 3, corresponding to 109 individually identified adult females or immatures of both sexes. Capture histories were built and analyzed using the Pollock's robust design capture‐mark‐recapture model. The study consisted of 13 primary periods sequenced in 5–8 secondary periods. Mean annual survival rate of residents was 0.945, 95% CI [0.864, 0.979]. Abundance varied between years from 75 to 35 individuals. The geometric growth rate over the period 2001–2013 was 0.938, 95% CI [0.878, 0.997], suggesting a population decline of −6.2%/year. Sperm whales are moving between Guadeloupe and Dominica, with a high temporary emigration rate (0.163) and 50% of the individuals of Guadeloupe resighted in Dominica. These results highlight the fragility of the population and the necessity to consider it as one unit.

The call of the emperor penguin: Legal responses to species threatened by climate change - Stephanie Jenouvrier; Judy Che‐Castaldo; Shaye Wolf; Marika Holland; Sara Labrousse; Michelle LaRue; Barbara Wienecke; Peter Fretwell; Christophe Barbraud; Noah Greenwald; Julienne Stroeve; Philip N. Trathan (Global Change Biology, 2021)
Species extinction risk is accelerating due to anthropogenic climate change, making it urgent to protect vulnerable species through legal frameworks in order to facilitate conservation actions that help mitigate risk. Here, we discuss fundamental concepts for assessing climate change risks to species using the example of the emperor penguin ( Aptenodytes forsteri ), currently being considered for protection under the US Endangered Species Act (ESA). This species forms colonies on Antarctic sea ice, which is projected to significantly decline due to ongoing greenhouse gas (GHG) emissions. We project the dynamics of all known emperor penguin colonies under different GHG emission scenarios using a climate‐dependent meta‐population model including the effects of extreme climate events based on the observational satellite record of colonies. Assessments for listing species under the ESA require information about how species resiliency, redundancy and representation (3Rs) will be affected by threats within the foreseeable future. Our results show that if sea ice declines at the rate projected by climate models under current energy system trends and policies, the 3Rs would be dramatically reduced and almost all colonies would become quasi‐extinct by 2100. We conclude that the species should be listed as threatened under the ESA.

Predation by feral cats threatens great albatrosses - Christophe Barbraud; Baudouin des Monstiers; Adrien Chaigne; Cédric Marteau; Henri Weimerskirch; Karine Delord (Biological Invasions, 2021)

Did the animal move? A cross-wavelet approach to geolocation data reveals year-round whereabouts of a resident seabird - Amédée Roy; Karine Delord; Guilherme T. Nunes; Christophe Barbraud; Leandro Bugoni; Sophie Lanco-Bertrand (Marine Biology, 2021)

Factors affecting adult body condition in the endangered northern rockhopper penguin - Karine Delord; Cédric Cotté; Pascal Terray; Charles-André Bost; Henri Weimerskirch; Christophe Barbraud (Marine Biology, 2021)

An observation of a gentoo penguin Pygoscelis papua feeding an Adélie penguin P. adeliae chick - Fabrice Genevois; Christophe Barbraud (Polar Biology, 2021)

Selection against immigrants in wild seabird populations - Christophe Barbraud; Karine Delord (Ecology Letters, 2021)
Immigration is a major demographic parameter shaping population dynamics and is an important driver of eco‐evolutionary patterns, but the fitness consequences for individuals following their settlement to a new population (immigrants) remain poorly tested in wild animal populations, particularly among long‐lived species. Here we show that immigrants have a lower fitness than residents in three wild seabird populations (wandering albatross Diomedea exulans , southern fulmar Fulmarus glacialoides , snow petrel Pagodroma nivea ). Across all species and during a 32‐year period, immigrants made on average −9 to 29% fewer breeding attempts, had 5–31% fewer fledglings, had 2–16% lower breeding success and produced 6–46% fewer recruits. Female immigration and male residency were also favored through differences in breeding performance. We provide evidence for selection against immigrants in wild populations of long‐lived species and our results are consistent with female‐biased dispersal in birds being driven by asymmetric limiting resources and the competitive ability of dispersers vs. non‐dispersers.

Population trends of penguins in the French Southern Territories - Christophe Barbraud; Karine Delord; Charles A. Bost; Adrien Chaigne; Cédric Marteau; Henri Weimerskirch (Polar Biology, 2020)

Sea ice predicts long‐term trends in Adélie penguin population growth, but not annual fluctuations: Results from a range‐wide multiscale analysis - David T. Iles; Heather Lynch; Rubao Ji; Christophe Barbraud; Karine Delord; Stephanie Jenouvrier (Global Change Biology, 2020)
Understanding the scales at which environmental variability affects populations is critical for projecting population dynamics and species distributions in rapidly changing environments. Here we used a multilevel Bayesian analysis of range‐wide survey data for Adélie penguins to characterize multidecadal and annual effects of sea ice on population growth. We found that mean sea ice concentration at breeding colonies (i.e., “prevailing” environmental conditions) had robust nonlinear effects on multidecadal population trends and explained over 85% of the variance in mean population growth rates among sites. In contrast, despite considerable year‐to‐year fluctuations in abundance at most breeding colonies, annual sea ice fluctuations often explained less than 10% of the temporal variance in population growth rates. Our study provides an understanding of the spatially and temporally dynamic environmental factors that define the range limits of Adélie penguins, further establishing this iconic marine predator as a true sea ice obligate and providing a firm basis for projection under scenarios of future climate change. Yet, given the weak effects of annual sea ice relative to the large unexplained variance in year‐to‐year growth rates, the ability to generate useful short‐term forecasts of Adélie penguin breeding abundance will be extremely limited. Our approach provides a powerful framework for linking short‐ and longer term population processes to environmental conditions that can be applied to any species, facilitating a richer understanding of ecological predictability and sensitivity to global change.

Do repeated captures and handling affect phenotype and survival of growing Snow Petrel (Pagodroma nivea)? - Sophie M. Dupont; Christophe Barbraud; Olivier Chastel; Karine Delord; Charline Parenteau; Cécile Ribout; Frédéric Angelier (Polar Biology, 2020)

Movements of three alcid species breeding sympatrically in Saint Pierre and Miquelon, northwestern Atlantic Ocean - Karine Delord; Christophe Barbraud; David Pinaud; Bruno Letournel; Baptiste Jaugeon; Herlé Goraguer; Pascal Lazure; Hervé Lormée (Journal of Ornithology, 2020)

The Paris Agreement objectives will likely halt future declines of emperor penguins - Stéphanie Jenouvrier; Marika Holland; David Iles; Sara Labrousse; Laura Landrum; Jimmy Garnier; Hal Caswell; Henri Weimerskirch; Michelle LaRue; Rubao Ji; Christophe Barbraud (Global Change Biology, 2020)
The Paris Agreement is a multinational initiative to combat climate change by keeping a global temperature increase in this century to 2°C above preindustrial levels while pursuing efforts to limit the increase to 1.5°C. Until recently, ensembles of coupled climate simulations producing temporal dynamics of climate en route to stable global mean temperature at 1.5 and 2°C above preindustrial levels were not available. Hence, the few studies that have assessed the ecological impact of the Paris Agreement used ad‐hoc approaches. The development of new specific mitigation climate simulations now provides an unprecedented opportunity to inform ecological impact assessments. Here we project the dynamics of all known emperor penguin ( Aptenodytes forsteri ) colonies under new climate change scenarios meeting the Paris Agreement objectives using a climate‐dependent‐metapopulation model. Our model includes various dispersal behaviors so that penguins could modulate climate effects through movement and habitat selection. Under business‐as‐usual greenhouse gas emissions, we show that 80% of the colonies are projected to be quasiextinct by 2100, thus the total abundance of emperor penguins is projected to decline by at least 81% relative to its initial size, regardless of dispersal abilities. In contrast, if the Paris Agreement objectives are met, viable emperor penguin refuges will exist in Antarctica, and only 19% and 31% colonies are projected to be quasiextinct by 2100 under the Paris 1.5 and 2 climate scenarios respectively. As a result, the global population is projected to decline by at least by 31% under Paris 1.5 and 44% under Paris 2. However, population growth rates stabilize in 2060 such that the global population will be only declining at 0.07% under Paris 1.5 and 0.34% under Paris 2, thereby halting the global population decline. Hence, global climate policy has a larger capacity to safeguard the future of emperor penguins than their intrinsic dispersal abilities.

The distribution, abundance, status and global importance of giant petrels (Macronectes giganteus and M. halli) breeding at South Georgia - Sally Poncet; Anton C. Wolfaardt; Christophe Barbraud; Ronnie Reyes-Arriagada; Andrew Black; Robert B. Powell; Richard A. Phillips (Polar Biology, 2020)

Prey remains of brown skua is evidence of the long-term decline in burrow occupancy of blue petrels and thin-billed prions at Mayes Island, Kerguelen - Nathan Pacoureau; Elie Gaget; Karine Delord; Christophe Barbraud (Polar Biology, 2019)

Scale matters: sea ice and breeding success of Adélie penguins - Emmanuelle Barreau; Yan Ropert-Coudert; Karine Delord; Christophe Barbraud; Akiko Kato-Ropert (Polar Biology, 2019)

Exposure of breeding albatrosses to the agent of avian cholera: dynamics of antibody levels and ecological implications - Amandine Gamble; Romain Garnier; Audrey Jaeger; Hubert Gantelet; Eric Thibault; Pablo Tortosa; Vincent Bourret; Jean-Baptiste Thiebot; Karine Delord; Henri Weimerskirch; Jérémy Tornos; Christophe Barbraud; et al. (Oecologia, 2019)

Population response of an apex Antarctic consumer to its prey and climate fluctuations - Nathan Pacoureau; Matthieu Authier; Karine Delord; Christophe Barbraud (Oecologia, 2019)

Reproductive performance and diving behaviour share a common sea‐ice concentration optimum in Adélie penguins ( Pygoscelis adeliae ) - Camille Le Guen; Akiko Kato; Ben Raymond; Christophe Barbraud; Michaël Beaulieu; Charles‐André Bost; Karine Delord; Andrew J. J. MacIntosh; Xavier Meyer; Thierry Raclot; Michael Sumner; Akinori Takahashi; et al. (Global Change Biology, 2018)
The Southern Ocean is currently experiencing major environmental changes, including in sea‐ice cover. Such changes strongly influence ecosystem structure and functioning and affect the survival and reproduction of predators such as seabirds. These effects are likely mediated by reduced availability of food resources. As such, seabirds are reliable eco‐indicators of environmental conditions in the Antarctic region. Here, based on 9 years of sea‐ice data, we found that the breeding success of Adélie penguins ( Pygoscelis adeliae ) reaches a peak at intermediate sea‐ice cover ( ca . 20%). We further examined the effects of sea‐ice conditions on the foraging activity of penguins, measured at multiple scales from individual dives to foraging trips. Analysis of temporal organisation of dives, including fractal and bout analyses, revealed an increasingly consistent behaviour during years with extensive sea‐ice cover. The relationship between several dive parameters and sea‐ice cover in the foraging area appears to be quadratic. In years of low and high sea‐ice cover, individuals adjusted their diving effort by generally diving deeper, more frequently and by resting at the surface between dives for shorter periods of time than in years with intermediate sea‐ice cover. Our study therefore suggests that sea‐ice cover is likely to affect the reproductive performance of Adélie penguins through its effects on foraging behaviour, as breeding success and most diving parameters share a common optimum. Some years, however, deviated from this general trend, suggesting that other factors (e.g. precipitation during the breeding season) might sometimes become preponderant over the sea‐ice effects on breeding and foraging performance. Our study highlights the value of monitoring fitness parameters and individual behaviour concomitantly over the long‐term to better characterize optimal environmental conditions and potential resilience of wildlife. Such an approach is crucial if we want to anticipate the effects of environmental change on Antarctic penguin populations.

Status and trends of albatrosses in the French Southern Territories, Western Indian Ocean - Henri Weimerskirch; Karine Delord; Christophe Barbraud; Fabrice Le Bouard; Peter G. Ryan; Peter Fretwell; Cédric Marteau (Polar Biology, 2018)

Two Recent Massive Breeding Failures in an Adélie Penguin Colony Call for the Creation of a Marine Protected Area in D'Urville Sea/Mertz - Yan Ropert-Coudert; Akiko Kato; Kozue Shiomi; Christophe Barbraud; Frédéric Angelier; Karine Delord; Timothée Poupart; Philippe Koubbi; Thierry Raclot (Frontiers in Marine Science, 2018)

First demographic insights on historically harvested and poorly known male sperm whale populations off the Crozet and Kerguelen Islands (Southern Ocean) - Guillemette Labadie; Paul Tixier; Christophe Barbraud; Rémi Fay; Nicolas Gasco; Guy Duhamel; Christophe Guinet (Marine Mammal Science, 2018)
Age and sex dependent spatial segregation has resulted in limited knowledge of the ecology and demography of sperm whale adult males feeding seasonally in high latitudes. This study focused on adult males interacting with the Patagonian toothfish ( Dissostichus eleginoides ) fishery operating off the Kerguelen and Crozet Archipelagos. Demographic parameters were estimated using a 10‐yr‐long photo‐identification data set paired with multistate closed robust design capture‐mark‐recapture models. The examination of a set of 29,078 photographs taken from fishing vessels during sperm whale depredation events resulted in identification of 295 individuals with nine visiting both study areas. Dispersal between both study regions was estimated to be 1% per year. The mean annual number of interacting sperm whales was estimated to n = 82 (95% CI 58–141) in Crozet and n = 106 (95% CI 76–174) in Kerguelen. Transient proportions were 13% in Crozet and 26% in Kerguelen. Corrected for transience, apparent survival estimates were 0.953 (95% CI 0.890–0.993) in Crozet, and 0.911 (95% CI 0.804–0.986) in Kerguelen. These survival and population size estimates are the first for depredating adult males in high latitudes, and can be used in evaluating the current conservation status of this historically harvested stock and to investigate depredation trends in 35 both Crozet and Kerguelen Islands.

Climatic influences on the breeding biology of the agile frog (Rana dalmatina) - Magali Combes; David Pinaud; Christophe Barbraud; Jacques Trotignon; François Brischoux (The Science of Nature, 2018)

High variability in migration and wintering strategies of brown skuas (Catharacta antarctica lonnbergi) in the Indian Ocean - Karine Delord; Yves Cherel; Christophe Barbraud; Olivier Chastel; Henri Weimerskirch (Polar Biology, 2018)

Demographic consequences of fisheries interaction within a killer whale (Orcinus orca) population - Paul Tixier; Christophe Barbraud; Deborah Pardo; Nicolas Gasco; Guy Duhamel; Christophe Guinet (Marine Biology, 2017)

Circumpolar analysis of the Adélie Penguin reveals the importance of environmental variability in phenological mismatch - Casey Youngflesh; Stephanie Jenouvrier; Yun Li; Rubao Ji; David G. Ainley; Grant Ballard; Christophe Barbraud; Karine Delord; Katie M. Dugger; Louise M. Emmerson; William R. Fraser; Jefferson T. Hinke; et al. (Ecology, 2017)
Evidence of climate‐change‐driven shifts in plant and animal phenology have raised concerns that certain trophic interactions may be increasingly mismatched in time, resulting in declines in reproductive success. Given the constraints imposed by extreme seasonality at high latitudes and the rapid shifts in phenology seen in the Arctic, we would also expect Antarctic species to be highly vulnerable to climate‐change‐driven phenological mismatches with their environment. However, few studies have assessed the impacts of phenological change in Antarctica. Using the largest database of phytoplankton phenology, sea‐ice phenology, and Adélie Penguin breeding phenology and breeding success assembled to date, we find that, while a temporal match between Penguin breeding phenology and optimal environmental conditions sets an upper limit on breeding success, only a weak relationship to the mean exists. Despite previous work suggesting that divergent trends in Adélie Penguin breeding phenology are apparent across the Antarctic continent, we find no such trends. Furthermore, we find no trend in the magnitude of phenological mismatch, suggesting that mismatch is driven by interannual variability in environmental conditions rather than climate‐change‐driven trends, as observed in other systems. We propose several criteria necessary for a species to experience a strong climate‐change‐driven phenological mismatch, of which several may be violated by this system.

Integrated population modeling reveals the impact of climate on the survival of juvenile emperor penguins - Fitsum Abadi; Christophe Barbraud; Olivier Gimenez (Global Change Biology, 2017)
Early‐life demographic traits are poorly known, impeding our understanding of population processes and sensitivity to climate change. Survival of immature individuals is a critical component of population dynamics and recruitment in particular. However, obtaining reliable estimates of juvenile survival (i.e., from independence to first year) remains challenging, as immatures are often difficult to observe and to monitor individually in the field. This is particularly acute for seabirds, in which juveniles stay at sea and remain undetectable for several years. In this work, we developed a Bayesian integrated population model to estimate the juvenile survival of emperor penguins ( Aptenodytes forsteri ), and other demographic parameters including adult survival and fecundity of the species. Using this statistical method, we simultaneously analyzed capture–recapture data of adults, the annual number of breeding females, and the number of fledglings of emperor penguins collected at Dumont d'Urville, Antarctica, for the period 1971–1998. We also assessed how climate covariates known to affect the species foraging habitats and prey [southern annular mode ( SAM ), sea ice concentration ( SIC )] affect juvenile survival. Our analyses revealed that there was a strong evidence for the positive effect of SAM during the rearing period ( SAMR ) on juvenile survival. Our findings suggest that this large‐scale climate index affects juvenile emperor penguins body condition and survival through its influence on wind patterns, fast ice extent, and distance to open water. Estimating the influence of environmental covariates on juvenile survival is of major importance to understand the impacts of climate variability and change on the population dynamics of emperor penguins and seabirds in general and to make robust predictions on the impact of climate change on marine predators.

Variation in the age of first reproduction: different strategies or individual quality? - Rémi Fay; Christophe Barbraud; Karine Delord; Henri Weimerskirch (Ecology, 2016)
Although age at first reproduction is a key demographic parameter that is probably under high selective pressure, it is highly variable and the cause of this variability is not well understood. Two non‐exclusive hypotheses may explain such variability. It could be the expression of different individual strategies, i.e., different allocation strategies in fitness components, or the consequences of individual difference in intrinsic quality, i.e., some individuals always doing better than others in all fitness components. We tested these hypotheses in the Wandering Albatross investigating relationships between the age at first reproduction and subsequent adult demographic traits. Using finite mixture capture recapture modeling, we demonstrate that the age at first reproduction is negatively related to both reproductive performances and adult survival, suggesting that individual quality was an important factor explaining variation in the age at first reproduction. Our results suggest that age at first breeding is a good predictor of quality in this long‐lived seabird species.

Seasonality in marine ecosystems: Peruvian seabirds, anchovy, and oceanographic conditions - Giannina Passuni; Christophe Barbraud; Alexis Chaigneau; Hervé Demarcq; Jesus Ledesma; Arnaud Bertrand; Ramiro Castillo; Angel Perea; Julio Mori; Vincent A. Viblanc; Jose Torres‐Maita; Sophie Bertrand (Ecology, 2016)
In fluctuating environments, matching breeding timing to periods of high resource availability is crucial for the fitness of many vertebrate species, and may have major consequences on population health. Yet, our understanding of the proximate environmental cues driving seasonal breeding is limited. This is particularly the case in marine ecosystems, where key environmental factors and prey abundance and availability are seldom quantified. The Northern Humboldt Current System ( NHCS ) is a highly productive, low‐latitude ecosystem of moderate seasonality. In this ecosystem, three tropical seabird species (the Guanay Cormorant Phalacrocorax bougainvillii , the Peruvian Booby Sula variegata , and the Peruvian Pelican Pelecanus thagus ) live in sympatry and prey almost exclusively on anchovy, Engraulis ringens . From January 2003 to December 2012, we monitored 31 breeding sites along the Peruvian coast to investigate the breeding cycle of these species. We tested for relationships between breeding timing, oceanographic conditions, and prey availability using occupancy models. We found that all three seabird species exhibited seasonal breeding patterns, with marked interspecific differences. Whereas breeding mainly started during the austral winter/early spring and ended in summer/early fall, this pattern was stronger in boobies and pelicans than in cormorants. Breeding onset mainly occurred when upwelling was intense but ecosystem productivity was below its annual maxima, and when anchovy were less available and in poor physiological condition. Conversely, the abundance and availability of anchovy improved during chick rearing and peaked around the time of fledging. These results suggest that breeding timing is adjusted so that fledging may occur under optimal environmental conditions, rather than being constrained by nutritional requirements during egg laying. Adjusting breeding time so that fledglings meet optimal conditions at independence is unique compared with other upwelling ecosystems and could be explained by the relatively high abundances of anchovy occurring throughout the year in the NHCS .

Factors affecting growth parameters of White Stork nestlings in eastern Algeria - Naouel Benharzallah; Abdelkrim Si Bachir; Fayçal Taleb; Christophe Barbraud (Journal of Ornithology, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Age, sex, and breeding status shape a complex foraging pattern in an extremely long‐lived seabird - Audrey Jaeger; Aurélie Goutte; Vincent J. Lecomte; Pierre Richard; Olivier Chastel; Christophe Barbraud; Henri Weimerskirch; Yves Cherel (Ecology, 2014)
Evidence of age‐dependent changes in foraging behavior of free‐ranging individuals is scarce, especially at older stages. Using the isotopic niche as a proxy of the trophic niche during both the breeding (blood) and inter‐nesting (feather) periods, we report here empirical evidence for age‐, gender‐, and breeding status‐dependent foraging ecology and examine its potential consequences on subsequent reproduction and survival in an extremely long‐lived species, the Wandering Albatross ( Diomedea exulans ). Immature Wandering Albatrosses of both sexes forage in the subtropics (δ 13 C) and feed at the same trophic position (δ 15 N) as the adults. In contrast to immature birds, adult females forage, on average, at more northern latitudes than males, with both sexes feeding in the subtropics during the inter‐nesting period, and males, not females, favoring subantarctic waters during incubation. In contrast to adult females, males show a unique pattern among birds and mammals of a continuous change with age in their main feeding habitat by foraging progressively farther south in colder waters during both the breeding and inter‐nesting periods. In males, foraging at higher latitudes (lower feather δ 13 C values) is associated with a lower probability of breeding during the following years compared to other birds, but with no effect on their probability of surviving. Foraging in cold and windy waters may be linked to foraging impairment that might explain different life history trade‐offs and lower investment in reproduction with age. This key point requires further longitudinal investigations and/or studies examining foraging success and the energy budget of birds feeding in different water masses.

Females better face senescence in the wandering albatross - Deborah Pardo; Christophe Barbraud; Henri Weimerskirch (Oecologia, 2013)

Using self-organizing maps to investigate environmental factors regulating colony size and breeding success of the White Stork (Ciconia ciconia) - Abdelkrim Si Bachir; Haroun Chenchouni; Nawel Djeddou; Christophe Barbraud; Régis Céréghino; Fréderic Santoul (Journal of Ornithology, 2013)

Evidence for an age‐dependent influence of environmental variations on a long‐lived seabird's life‐history traits - Deborah Pardo; Christophe Barbraud; Matthieu Authier; Henri Weimerskirch (Ecology, 2013)
Theoretical and empirical studies have highlighted the effects of age on several life‐history traits in wild populations. There is also increasing evidence for environmental effects on their demographic traits. However, quantifying how individuals differentially respond to environmental variations according to their age remains a challenge in ecology. In a population of Black‐browed Albatrosses monitored during 43 years, we analyzed how life‐history traits varied according to age, and whether individuals of different ages responded in different ways to environmental conditions. To do so, we: (1) examined how age affected seven life‐history traits, (2) investigated differences in temporal variance of demographic traits between age classes, and (3) tested for age‐dependent effects of climate and fisheries covariates on demographic traits. Overall, there was a tendency for traits to improve during the first years of life (5–10 years), to peak and remain stable at middle age (10–30 years), and decline at old ages. At young ages, survival and reproductive parameters increased, except offspring body condition at fledging, suggesting that younger parents had already acquired good foraging capacities. However, they suffered from inexperience in breeding as suggested by their higher breeding failures during incubation. There was evidence for reproductive and actuarial senescence. In particular, breeding success and offspring body condition declined abruptly, suggesting altered foraging capacities of old individuals. Middle‐aged individuals had the lowest temporal variance of demographic traits. Although this is predicted by the theory of environmental canalization, it could also results from a higher susceptibility of young and old birds due to their respective inexperience and senescence. The highest temporal variances were found in old individuals. Survival was significantly influenced by sea surface temperatures in the foraging zone of this albatross population during breeding. During warm events survival of young and old individuals improved, whereas a decrease was observed for middle‐aged individuals. Presumably, during cold years with poor environmental conditions, young and old breeding birds may suffer more from intraspecific competition for resources than middle‐aged individuals. This study showed that age, known as a major factor structuring demography in long‐lived species, can also potentially influence the response of populations to global change.

Effects of climate change on an emperor penguin population: analysis of coupled demographic and climate models - Stéphanie Jenouvrier; Marika Holland; Julienne Stroeve; Christophe Barbraud; Henri Weimerskirch; Mark Serreze; Hal Caswell (Global Change Biology, 2012)
Sea ice conditions in the A ntarctic affect the life cycle of the emperor penguin ( A ptenodytes forsteri ). We present a population projection for the emperor penguin population of T erre A délie, A ntarctica, by linking demographic models (stage‐structured, seasonal, nonlinear, two‐sex matrix population models) to sea ice forecasts from an ensemble of IPCC climate models. Based on maximum likelihood capture‐mark‐recapture analysis, we find that seasonal sea ice concentration anomalies ( SIC a ) affect adult survival and breeding success. Demographic models show that both deterministic and stochastic population growth rates are maximized at intermediate values of annual SIC a , because neither the complete absence of sea ice, nor heavy and persistent sea ice, would provide satisfactory conditions for the emperor penguin. We show that under some conditions the stochastic growth rate is positively affected by the variance in SIC a . We identify an ensemble of five general circulation climate models whose output closely matches the historical record of sea ice concentration in T erre A délie. The output of this ensemble is used to produce stochastic forecasts of SIC a , which in turn drive the population model. Uncertainty is included by incorporating multiple climate models and by a parametric bootstrap procedure that includes parameter uncertainty due to both model selection and estimation error. The median of these simulations predicts a decline of the T erre A délie emperor penguin population of 81% by the year 2100. We find a 43% chance of an even greater decline, of 90% or more. The uncertainty in population projections reflects large differences among climate models in their forecasts of future sea ice conditions. One such model predicts population increases over much of the century, but overall, the ensemble of models predicts that population declines are far more likely than population increases. We conclude that climate change is a significant risk for the emperor penguin. Our analytical approach, in which demographic models are linked to IPCC climate models, is powerful and generally applicable to other species and systems.

Assessing the effect of satellite transmitters on the demography of the Wandering Albatross Diomedea exulans - Christophe Barbraud; Henri Weimerskirch (Journal of Ornithology, 2012)

Estimating survival and reproduction in a quasi-biennially breeding seabird with uncertain and unobservable states - Christophe Barbraud; Henri Weimerskirch (Journal of Ornithology, 2012)

Bet‐hedging response to environmental variability, an intraspecific comparison - Marie Nevoux; Jaume Forcada; Christophe Barbraud; John Croxall; Henri Weimerskirch (Ecology, 2010)
A major challenge in ecology is to understand the impact of increased environmental variability on populations and ecosystems. To maximize their fitness in a variable environment, life history theory states that individuals should favor a bet‐hedging strategy, involving a reduction of annual breeding performance and an increase in adult survival so that reproduction can be attempted over more years. As a result, evolution toward longer life span is expected to reduce the deleterious effects of extra variability on population growth, and consequently on the trait contributing the most to it (e.g., adult survival in long‐lived species). To investigate this, we compared the life histories of two Black‐browed Albatross ( Thalassarche melanophrys ) populations breeding at South Georgia (Atlantic Ocean) and Kerguelen (Indian Ocean), the former in an environment nearly three times more variable climatically (e.g., in sea surface temperature) than the latter. As predicted, individuals from South Georgia (in the more variable environment) showed significantly higher annual adult survival (0.959, SE = 0.003) but lower annual reproductive success (0.285 chick per pair, SE = 0.039) than birds from Kerguelen (survival = 0.925, SE = 0.004; breeding success = 0.694, SE = 0.027). In both populations, climatic conditions affected the breeding success and the survival of inexperienced breeders, whereas the survival of experienced breeders was unaffected. The strength of the climatic impact on survival of inexperienced breeders was very similar between the two populations, but the effect on breeding success was positively related to environmental variability. These results provide rare and compelling evidence to support bet‐hedging underlying changes in life history traits as an adaptive response to environmental variability.

Interdecadal changes in at‐sea distribution and abundance of subantarctic seabirds along a latitudinal gradient in the Southern Indian Ocean - CLARA PÉRON; MATTHIEU AUTHIER; CHRISTOPHE BARBRAUD; KARINE DELORD; DOMINIQUE BESSON; HENRI WEIMERSKIRCH (Global Change Biology, 2010)
Long‐term demographic studies have recently shown that global climate change together with increasing direct impacts of human activities, such as fisheries, are affecting the population dynamics of marine top predators. However, the effects of these factors on species distribution and abundance at sea are still poorly understood, particularly in marine ecosystems of the southern hemisphere. Using a unique long‐term data set of at‐sea observations, we tested for interdecadal (1980s vs. 2000s) changes in summer abundance and distribution of 12 species of Albatrosses and Petrels along a 30° latitudinal gradient between tropical and Antarctic waters of the southern Indian Ocean. There were contrasting effects of climate change on subantarctic seabird distribution and abundance at sea. While subtropical waters showed the highest rate of warming, the species that visited this water mass showed the greatest changes in distribution and abundance. The abundance of Wandering Albatrosses ( Diomedea exulans ), White‐chinned Petrels ( Procellaria aequinoctialis ) and Giant Petrels ( Macronectes sp.) declined markedly, whereas the other species showed contrasting trends or did not change. With the exception of the White‐chinned Petrel, these decreases were at least partly related to regional increase in sea surface temperature. The southward shift of Wandering Albatross and Prions ( Pachyptila spp.) distributions could be ascribed to species redistribution or decrease in abundance due to warming of the subtropical waters. Surprisingly, White‐chinned Petrel distribution shifted northward, suggesting more complex mechanisms. This study is the first to document a shift in species range in the Southern Ocean related to climate change and contrasting abundance changes. It suggests that some species might experience more severe impacts from climate change depending on the water masses they visit. As climate changes are predicted to continue in the next decades, understanding species responses to climate change is crucial for conservation management, especially when their conservation status is critical or unknown.

Relative influence of fisheries and climate on the demography of four albatross species - VIRGINIE ROLLAND; HENRI WEIMERSKIRCH; CHRISTOPHE BARBRAUD (Global Change Biology, 2010)
Worldwide ecosystems are modified by human activities and climate change. To be able to predict future changes, it is necessary to understand their respective role on population dynamics. Among the most threatened species are top predators because of their position in the food web. Albatross populations are potentially affected by both human activities, especially longline fisheries, and climatic fluctuations. Based on long‐term data (1985–2006), we conducted through a comparative approach a demographic analysis (adult survival and breeding success) on four albatross species breeding on the Indian Ocean sub‐Antarctic Islands to assess the relative impact of climate and fisheries during and outside the breeding season. The study revealed that adult survival of almost all species was not affected by climate, and therefore probably canalized against climatic variations, but was negatively affected by tuna longlining effort in three species. Breeding success was affected by climate, with contrasted effects between species, with Southern Oscillation Index having an impact on all species but one. Differences in demographic responses depended on the foraging zone and season. In order to predict population trajectories of seabirds such as albatrosses, our results show the importance of assessing the relative influence of fishing and climate impacts on demography.

Multivariate effects on seabird bycatch in the legal Patagonian toothfish longline fishery around Crozet and Kerguelen Islands - Karine Delord; Nicolas Gasco; Christophe Barbraud; Henri Weimerskirch (Polar Biology, 2010)

Long- and short-term influence of environment on recruitment in a species with highly delayed maturity - Marie Nevoux; Henri Weimerskirch; Christophe Barbraud (Oecologia, 2010)

Relationships between sea ice concentration, sea surface temperature and demographic traits of thin-billed prions - Marie Nevoux; Christophe Barbraud (Polar Biology, 2006)

Sea ice affects the population dynamics of Adélie penguins in Terre Adélie - Stephanie Jenouvrier; Christophe Barbraud; Henri Weimerskirch (Polar Biology, 2006)

Long-term trends in the population size of king penguins at Crozet archipelago: environmental variability and density dependence? - Karine Delord; Christophe Barbraud; Henri Weimerskirch (Polar Biology, 2004)

Effect of sea-ice extent on adult survival of an Antarctic top predator: the snow petrel Pagodroma nivea - Christophe Barbraud; Henri Weimerskirch; Christophe Guinet; Pierre Jouventin (Oecologia, 2000)

Early body condition and hatching success in the snow petrel Pagodroma nivea - Christophe Barbraud; Olivier Chastel (Polar Biology, 1999)